2013
DOI: 10.3109/10826084.2013.841250
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Symptom Severity Indicators of Alcohol Dependence and the Personality Concept of the Biosocial Model

Abstract: Temperament and character factors are strongly related to the developmental, clinical, and treatment aspects of alcohol dependence. This study had the aim of revealing the underlying personality structure and individual differences in the symptoms of alcohol dependence measured by multiple severity indicators. Patients with alcohol dependence exhibited higher levels of novelty seeking and harm avoidance, and lower levels of persistence, self-directedness, and cooperativeness. Especially novelty seeking was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Because pathologies that underlie comorbid personality traits may contribute or have an effect on the course or prognosis of AD, specific personality traits may reflect a genetic predisposition for substance abuse [ 26 , 27 ]. Our patients with AD had higher NS and HA scores compared to the healthy controls, findings that are in line with those from an earlier study [ 28 ]. In our subgroup analysis, we found that patients with EOAD had the highest NS scores, followed by patients with LOAD, and controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Because pathologies that underlie comorbid personality traits may contribute or have an effect on the course or prognosis of AD, specific personality traits may reflect a genetic predisposition for substance abuse [ 26 , 27 ]. Our patients with AD had higher NS and HA scores compared to the healthy controls, findings that are in line with those from an earlier study [ 28 ]. In our subgroup analysis, we found that patients with EOAD had the highest NS scores, followed by patients with LOAD, and controls.…”
Section: Discussionsupporting
confidence: 93%
“…Personality factors may be major predictors for either the course or the outcome of AD [ 26 , 27 ]. Using the model of Cloninger’s biosocial theory of personality, patients with AD have higher novelty seeking (NS) and harm avoidance (HA) scores than that found in controls [ 28 ]. Studies have found an association between the SLC6A3 gene and personality traits defined by the Cloninger’s model in healthy individuals [ 29 , 30 ] and patients with depression [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dopaminergic system and specific personality traits have been implicated in the development of AD [ 7 , 16 , 47 ]; however, the relationship between DAT availability and personality in AD has received very little attention. The present study found that patients with AD displayed higher NS and HA traits than healthy controls, in agreement with a previous study [ 16 ]. Additionally, the present study found that among patients with AD, high HA was related to high brain DAT availability ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is implicated in the regulation of specific personality traits [ 16 , 17 ], and dopamine transporter/receptor availability may also be associated with certain traits [ 18 , 19 ]. However, the relationship between DAT availability and personality has not been clearly established either among healthy subjects or patient populations [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed as well that students taking narcotics manifest, as a major feature of themselves, a higher level of novelty seeking, and a lower level of persistence and of self-directedness, in comparison with their peers who neither take narcotics nor intend to do so (Chodkiewicz, 2007;Hornowska, 2003). The dimension of novelty seeking, which, on the basis of numerous studies, has come to be considered to be a significant risk factor for the occurrence and the permanence of the majority of addictions, was connected with the exacerbation of the alcohol problems as well (Andó et al, 2014), whereas self-directedness manifested negative associations with the occurrence of personality disorders in the case of alcoholics (Basiaux et al, 2001). A higher level of novelty seeking was also a major feature of alcoholics commencing addictive drinking early in comparison with those who started to drink intensively later (Dom, Hulsijn, & Sabbe, 2006).…”
Section: Introductionmentioning
confidence: 99%